Evaluating Soybean Meal Quality Using Near-Infrared Reflectance Spectroscopy - K. M. Dunmire; J. Dhakal; K. Stringfellow; C. R. Stark; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2019)
The objective of this study was to establish a range of soybean meal quality to evaluate the correlations between official analytical methods and near-infrared reflectance spectroscopy (NIRS). Crushed soybean white flakes (Mark Hershey Farms, Lebanon, PA) exposed to mechanical oil extraction, but not heat processing, were used in this experiment. Ground samples (500 g) were put into cotton bags and autoclaved at 262°F for 0, 5, 10, 15, 30, 45, and 60 min at 29 PSI. This was done to simulate varying degrees of heat processing. A total of 2 samples per treatment were autoclaved in 3 separate blocks. The duplicate samples were divided and analyzed using NIRS and official analytical analysis (wet chemistry). Crude protein (CP), total lysine (Lys), Lys:CP, available Lys, available Lys:total Lys, protein solubility in potassium hydroxide (KOH), trypsin inhibitor activity (TIA), urease activity index (UAI), individual amino acids (AA), and total AA were analyzed to determine the degree of processing using official analytical methods. The correlation coefficient (R) and coefficient determination (r2) between NIRS and official analytical methods were established for CP, total Lys, available/reactive Lys, Lys:CP and available/reactive Lys:total Lys. Data were analyzed using the SAS (v. 9.4, SAS Institute Inc., Cary, NC) GLIMMIX procedure and the CORR procedure to determine the degree of association of NIRS and official analytical analysis. When measured using official analytical methods, CP, total AA, Ala, Asp, Glu, Gly, Iso, Leu, and Val decreased (linear,P<0.05), whereas available/reactive Lys:total Lys, Lys:CP, available Lys, KOH, trypsin inhibitor, urease, Lys, and Cys decreased (quadratic,P<0.05) with increasing exposure time to the autoclave. There was a positive correlation between official analytical and NIRS results for CP, Lys:CP, available Lys:total Lys, total AA, Ala, Cys, Lys, and a negative correlation for Thr. A linear model was best fit (P= 0.011, r2= 0.489) to predict CP using NIRS. A quadratic model was best fit to use NIRS total Lys (P= 0.011, r2= 0.969), reactive Lys (P= 0.001, r2= 0.988), and their ratio (P= 0.001, r2= 0.981) to predict official analytical results. In conclusion, increasing soybean autoclave exposure time decreased soybean meal quality as measured by crude protein, total Lys, Lys:CP, available Lys, available Lys:total Lys, KOH solubility total AA, and additional AA. In addition, regression models were successful at using NIRS for Lys, reactive Lys, Lys:CP, and reactive Lys:total Lys to predict official analytical results.
Keywords: soybeans; soybean meal; heat processing; NIR; lysine; available lysine